Endoscopic expand transnasal approach to the suprasellar region ： anatomical study and clinical considerations - Lu, Xiao-jie; Chen, Kai-lai; Wang, Qin; Ji, Wei-yang; Li, Bing; Sun, Ji-yong; Li, Jiang-an (Chinese medical journal, 2009)
Backgroud The expanded endonasal approach （EEA） is used sparingly by surgeons for resection of lesions in the ventrocranial base. Herein, we examined the anatomy of the ventrocranial base by endoscopy and comment on the use of EEA in clinical practice. Methods Twenty artery-injected adult cadaveric heads were studied under surgical conditions using the endoscopic EEA. The extent of the surgical exposure, the endoscopic anatomic view and the maneuverability of surgical instruments about the suprasellar region were studied by the endoscopic EEA. Results The EEA by endoscope can reach the suprasellar region. In this approach, the optocarotid recess, supra and infra-optic chiasm interspace, the ophthalmic artery and others were important anatomical landmarks for identification of the suprasellar region. Conclusions The endoscopic EEA can be used to remove many types of lesions in the ventrocranial base. The microanatomy observed using the endoscope provides important anatomical information on the suprasellar region for neurosurgeons.